A high-density genome-wide approach reveals novel genetic markers linked to small ruminant lentivirus susceptibility in sheep - Riggio, Silvia; Tolone, Marco; Sottile, Gianluca; Tumino, Serena; Portolano, Baldassare; Sutera, Anna Maria; Sardina, Maria Teresa; Cesarani, Alberto; Mastrangelo, Salvatore (Frontiers in Genetics, 2024)
Visna/Maedi virus (VMV) is lentiviral disease of sheep responsible for severe production losses. Multiple genomic regions associated with infection were reported indicating genetic complexity. In this study, a combined genome-wide approach using a high-density SNP array has been performed, comparing VMV-infected (n=78) and non-infected (n=66) individuals of the Valle del Belice breed. The serological tests showed a seroprevalence of 26%. The comparison among results from different approaches (GWAS, Fisher's exact test and the FST analysis) revealed two association signals: on OAR03 close to the GRIN2B gene and on OAR05 close to the TMEM232 gene. To the best of our knowledge, there has been no previous association between these genes and lentiviral infection in any species. The GRIN2B gene plays a role in pain response, synaptic transmission, and receptor clustering, while TMEM232 is involved in the development of immune-related disorders. The results highlighted new aspects of the genetic complexity related to the resistance/susceptibility to VMV in sheep, confirming that studies on different breeds can lead to different results. The ideal approach for validation of the markers identified in our study is to use samples from a population independent from the discovery population with the same phenotype used in the discovery stage.